Bartók and His World - Laki, Péter 1954-; Laki, Péter 1954-; Botstein, Leon 1946-; Csoóri, Sándor 1930-2016; Devecseri, Gábor 1917-1971; Illyés, Gyula 1902-1983; Kassák, Lajos 1887-1967; Károlyi, Amy 1909-2003; Képes, Géza 1909-1989; Adorno, Theodor W. 1903-1969; Voit, Pál 1909-1988; Lampert, Vera 1944-; et al. (Princeton University Press, 2021)
Béla Bartók, who died in New York fifty years ago this September, is one of the most frequently performed twentieth-century composers. He is also the subject of a rapidly growing critical and analytical literature. Bartók was born in Hungary and made his home there for all but his last five years, when he resided in the United States. As a result, many aspects of his life and work have been accessible only to readers of Hungarian. The main goal of this volume is to provide English-speaking audiences with new insights into the life and reception of this musician, especially in Hungary. Part I begins with an essay by Leon Botstein that places Bartók in a large historical and cultural context. László Somfai reports on the catalog of Bartók's works that is currently in progress. Peter Laki shows the extremes of the composer's reception in Hungary, while Tibor Tallián surveys the often mixed reviews from the American years. The essays of Carl Leafstedt and Vera Lampert deal with his librettists Béla Balázs and Melchior Lengyel respectively. David Schneider addresses the artistic relationship between Bartók and Stravinsky. Most of the letters and interviews in Part II concern Bartók's travels and emigration as they reflected on his personal life and artistic evolution. Part III presents early critical assessments of Bartók's work as well as literary and poetic responses to his music and personality
Description based on online resource; title from PDF title page (publisher's Web site, viewed 31. Mrz 2021)
Keywords: MUSIC / History & Criticism